A Modification of the Fibular Osteotomy for Total Ankle Replacement Through the Lateral Transfibular Approach. (20th November 2019) - Usuelli, Federico G.; Indino, Cristian; Maccario, Camilla; Manzi, Luigi; Romano, Fausto; Aiyer, Amiethab; Kaplan, Jonathan R.M.
Abstract : Background: One disadvantage of lateral transfibular total ankle arthroplasty is the rate of symptoms related to the implant and wound issues requiring implant removal in association with the traditional fibular osteotomy. In the present study, lateral total ankle arthroplasty involving the traditional short oblique fibular osteotomy was compared with arthroplasty involving a long oblique osteotomy (the Foot & Ankle Reconstruction Group osteotomy). Methods: We retrospectively reviewed all primary lateral total ankle arthroplasties that had been performed by a single surgeon from May 2013 to October 2016 and had a minimum of 2 years of follow-up. Clinical assessment included patient demographics, wound complications, the need for implant removal, the pain score on a visual analog scale, the American Orthopaedic Foot & Ankle Society score, and the Short Form-12 Mental and Physical Component Summary scores. Weight-bearing radiographs were used to assess tibiotalar alignment, implant alignment, and fibular osteotomy healing. Results: One hundred and fifty-nine total ankle arthroplasties were identified. The traditional short fibular osteotomy was used in 50 ankles, and the long oblique osteotomy was used in 109. The rate of survival of the tibial and talar components of the ankle replacements was 100%, and there were no osteotomy nonunions. There was improvement in all clinical parameters, with no significant difference between the 2 groups. Radiographs showed excellent arthroplasty alignment at all time points, with no significant difference between the groups. There was a significant difference in the rates of wound dehiscence (p = 0.011) and fibular implant removal (p < 0.0001), with the long oblique osteotomy having lower rates of both (2.8% and 2.8%, respectively) compared with the short oblique osteotomy (14% and 28%, respectively). Conclusions: In total ankle arthroplasty, modification of the traditional short oblique fibular osteotomy to a long oblique configuration provided excellent 2-year survival rates with good clinical and radiographic outcomes and decreased rates of wound complications and symptoms related to the fibular implant. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.